Placing of the Onboard Equipment of Space Vehicles Taking the Influence of External Factors into Account. (2017) - Shulepov, A.I.
Abstract: In the design process, when placing the on-board equipment of a spacecraft in the compartments of a minimum volume, along with the design and technological constraints the possible impact of the space environment must be taken into account. These are classified in the literature as a means of impact energy directed at the spacecraft transmission during its intended operation. As such, damaging factors most often considered are a means of mechanical action of meteoric and man-made particles. The energy released in the surface layer structure from the effects of other power transmission means or penetrating its material (different types of beam funds), as well as the energy of the electromagnetic pulse can disrupt the normal functioning of the onboard spacecraft equipment Protection of aircraft equipment by means of energy transfer napavlennoy determines the reliability of the spacecraft functioning and efficiency of the performance of the flight plan. In this paper the mathematical formulation and method of solving the problem of finding dense layouts spacecraft through proper allocation of the onboard equipment inside compartments for the effect on the spacecraft factors directed energy transfer.